Exposure to natalizumab throughout pregnancy: effectiveness and safety in an Italian cohort of women with multiple sclerosis. Issue 12 (30th September 2022) - Landi, Doriana; Bovis, Francesca; Grimaldi, Alfonso; Annovazzi, Pietro Osvaldo; Bertolotto, Antonio; Bianchi, Alessia; Borriello, Giovanna; Brescia Morra, Vincenzo; Bucello, Sebastiano; Buscarinu, Maria Chiara; Caleri, Francesca; Capobianco, Marco; et al.
Abstract : Objective: Assessing the risk of clinical and radiological reactivation during pregnancy and post partum in women with multiple sclerosis (MS) treated with natalizumab (NTZ) throughout pregnancy (LONG_EXP) compared with women interrupting treatment before (NO_EXP) and within >−30 days and ≤90 days from conception (SHORT_EXP), and describing newborns' outcomes. Methods: Maternal clinical and radiological outcomes and obstetric and fetal outcomes were retrospectively collected and compared among groups (NO_EXP, SHORT_EXP, LONG_EXP). Predictors of clinical and radiological reactivation were investigated through univariable and multivariable analysis. Results: 170 eligible pregnancies from 163 women referring to 29 Italian MS centres were included. Annualised relapse rate (ARR) was significantly lower in LONG_EXP (n=66, 0.02 (0.001–0.09)) compared with NO_EXP (n=31, 0.43 (0.21–0.75), p=0.002) and SHORT_EXP (n=73, 0.46 (0.30–0.66), p=0.0004) during pregnancy, and in LONG_EXP (0.12 (0.05–0.24)) compared with SHORT_EXP (0.30 (0.17–0.50), p=0.008) during post partum. Gadolinium-enhancing (Gd+) lesions were less frequent in LONG_EXP (n=6/50, 2.00%) compared with NO_EXP (n=9/21, 42.86%) and SHORT_EXP after delivery (n=17/49, 34.69%, p=0.010). Delaying NTZ resumption after delivery significantly increased the risk of relapses (OR=1.29 (95% CI 1.07 to 1.57), p=0.009) and Gd+ lesions (OR=1.49 (95% CI 1.17 to 1.89, p=0.001). Newborns' weight, length, head circumference and gestational age did not differ among groups after adjusting for confounders. Anaemia was tracked in 4/69 LONG_EXP newborns. Congenital anomaly rate was within the expected range for the untreated MS population. Conclusions: Our findings indicate that in women with MS treated with NTZ before conception, continuation of NTZ throughout pregnancy and its early resumption after delivery mitigate the risk of clinical and radiological reactivation. This approach has no major impact on newborns' outcomes.